2016
DOI: 10.1002/cbic.201500572
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Utilization of Pelargonidin and Indole for the Biosynthesis of Plant Indole Alkaloids

Abstract: Nudicaulins are a group of indole alkaloid glycosides responsible for the color of yellow petals of Papaver nudicaule (Iceland poppy). The unique aglycone scaffold of these alkaloids attracted our interest as one of the most unusual flavonoid‐indole hybrid structures that occur in nature. Stable isotope labeling experiments with sliced petals identified free indole, but not tryptamine or l‐tryptophan, as one of the two key biosynthetic precursors of the nudicaulin aglycone. Pelargonidin was identified as the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 22 publications
1
32
0
1
Order By: Relevance
“…Although indole is consumed in the biosynthesis of nudicaulins, its level increased, though not to a statistically significant degree, during the development of yellow petals ( p =0.067). A previous study revealed that the maximum level of indole in yellow petals is reached shortly before flowering . These results suggest that, in yellow flowers, more indole is produced than is used for the synthesis of nudicaulins, and so it is emitted as a floral volatile.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…Although indole is consumed in the biosynthesis of nudicaulins, its level increased, though not to a statistically significant degree, during the development of yellow petals ( p =0.067). A previous study revealed that the maximum level of indole in yellow petals is reached shortly before flowering . These results suggest that, in yellow flowers, more indole is produced than is used for the synthesis of nudicaulins, and so it is emitted as a floral volatile.…”
Section: Resultsmentioning
confidence: 76%
“…Although their biosynthesis is not well studied, some reports suggest that they are products of the phenylpropanoid biosynthetic pathway . In P. nudicaule , this route is active during the production of pelargonidin, thus suggesting a second biochemical connection between floral volatiles and pigments in the flowers of this species.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations